PT Anbira Permata Teknologi - Yosa Nugraha Firmana; Ricky Setiawan; Theofilus Benaya; Yosua Leonardo; Denny Fian; Kanisius Dimas; Huswatun Nurmaningsih (AIBPM Publisher, 2018)
Exports are the sale of goods abroad using the payment system, quality, quantity and other conditions that have been issued by exporters and importers. The export process is an action to issue goods or goods from within the country to enter them into other countries. By doing export, it can produce various benefits, especially increasing foreign exchange. Export activity is one of the courses that can be found at Ma Chung University, through this course it can provide benefits to increase existing exports, things that encourage students in compiling a series of exports to be carried out. Re-activation can provide benefits for companies to export. PT. Anbira Permata Teknologi is a company engaged in technology, through PT. Anbira Permata Teknologi Ma Chung University especially our group is able to provide about the plan for exporting their own product. One of the product that can be used is LISSE and also this thing could be exported, this LISSE product has several imported raw materials that can be improved in quality. Therefore the export course with the theme